FACTORS AFFECTING STUDENTS’ SPEAKING PARTICIPATION (A Descriptive Study at Year-12 of SMKK Immanuel 2 Kuburaya) - Deoselly Mantari Kasih Panjaitan; Sudarsono Sudarsono; Yanti Sri Rezeki (Universitas Tanjungpura, 2019)
AbstractThe aim of this study was to measure the frequency of students’ participation and factors affecting the participation and conducted using a descriptive method. The researcher used 2 categories of the questionnaire with 28 closed questions, observation and interview. The questions were put in Ratio Scale focusing on the students' opinion toward their participation. The observation was done twice in two weeks and continued to interview section where 10 students were taken to be interviewed. The study took place in SMKK Immanuel Kubu Raya and the participants were thirty-eight students from grade XII Marketing. The data was analyzed using formulas designed for counting the frequency of participation. For observation and interview, the analysis was done by coding and classification. Based on the calculation, the score showed that the students’ participation tended to be normal to high. Factors affecting the students were divided into 3 areas; psychological, environmental and linguistic factors consisted of the lack of vocabulary followed by topical knowledge which affect the students the most. In conclusion, the students have good participation in English but are still affected by their vocabulary mastery and topical knowledge. Keywords: Factors Affecting Students’ Low Participation, English Speaking Subject, Participation